PENGARUH FAKTOR INTERNAL MAHASISWA TERHADAP PARTISIPASI MAHASISWA DALAM TUTORIAL ONLINE - Susanti, Susanti (LPPM Universitas Terbuka, 2007)
The optimal learning process conducted by students will reflect the result in their study evaluation. The final score of the subject is determined by two important components: Tutorial (60%) and final exam (40%). Student’s participation in online tutorial (tuton) contributes 10% and 50% for tutorial assignments. Because of the students’ participation in online tutorial (tuton) decreases, whereas it gives a significant contribution, there are a number of factors causing the limit number of students participation. This factor, temporary, is considered by the cause of the student’s internal problems. This research is aimed at analyzing the impact of student’s internal problems to his/her participation in tuton. This is a descriptive qualitative research using purposive informant. Data gained by having an in-depth interview, questionnaire, and observations. The data were analyzed by conducting data category process, data reduction, data display, data interpretation, and data analysis. The results show that student’s internal factor: the low ability in using learning technology and students activity, have a significant impact to his/her participation in tuton